The influence of socio-economic factors on behavioral intention to use mobile phones among fishermen in Pangkor Island - Mazuki, Raidah; Omar, Siti Zobidah; Bolong, Jusang; Alby, Jeffrey Lawrence D'Silva; Abu Hassan, Musa; Mohamed Shaffril, Hayrol Azril (Medwell Journals, 2013)
The focus of this study is to examine whether socio-economic factors (age, income per month, level of education, days spent at sea, fishermen category and experience as a fisherman) influence behavioral intention regarding the usage of mobile phones among fishermen in Pangkor Island. A total of 250 questionnaires were given to fishermen on the island. For the purposes of analyses, descriptive statistics such as frequency, percentage and mean were employed. Further analysis using independent t-test and Pearson product moment correlation were also performed to determine any significant differences and relationships arising. The results confirm that fishermen in Pangkor Island have favorable behavioral intentions towards mobile phone usage. Further analysis reveals that fishermen with different levels of education possess different behavioral intentions towards mobile phone usage. It can be noted that the factors of age and days spent at sea recorded significant and negative relationships with behavioral intention towards mobile phone usage. A number of discussions are conducted and these can be used by students, researchers and government officers for further studies within the field.